Challenges in establishing animal models for studying osteoimmunology of hypoparathyroidism - Butylina, Maria; Föger-Samwald, Ursula; Gelles, Katharina; Pietschmann, Peter; Sipos, Wolfgang (Frontiers in Veterinary Science, 2023)
Hypoparathyroidism is a relatively rare human (and veterinary) disease characterized by deficient or absent production of parathyroid hormone (PTH). PTH is known as a classical regulator of calcium and phosphorus homeostasis. Nevertheless, the hormone also appears to modulate immune functions. For example, increased CD4:CD8 T cell ratios as well as elevated interleukin (IL)-6 and IL-17A levels were observed in patients with hyperparathyroidism, whereas gene expression of tumor necrosis factor-α (TNF-α) and GM-CSF were decreased in patients with chronic postsurgical hypoparathyroidism. Various immune cell populations were affected differently. So, there is a need for validated animal models for the further characterization of this disease for identifying targeted immune-modulatory therapies. In this review we discuss the challenges in establishing animal models of hypoparathyroidism and compare rodents with large animal species with respect to this purpose.Besides genetically modified mouse models of hypoparathyroidism, there are surgical rodent models. Parathyroidectomy (PTX) can be well performed in rats – for pharmacological and associated osteoimmunological research and bone mechanical studies, a large animal model could be preferable, however. A major draw-back for successfully performing total PTX in large animal species (pigs, sheep) is the presence of accessory glands, thus demanding to develop new approaches for real-time detection of all parathyroid tissues.